Age-related changes in time production and reproduction tasks: Involvement of attention and working memory processes. Issue 3 (3rd May 2020) - Mioni, Giovanna; Capizzi, Mariagrazia; Stablum, Franca
ABSTRACT: Several studies have reported age-related differences in time estimation, which have been attributed either to a slowing of the pacemaker rate with aging or to impaired attention and/or working resources in older adults. Here, we compared performance of young and older participants on time production/reproduction tasks and on working memory, divided attention, sustained attention and executive attention tasks. Results showed that relative to young participants, older adults significantly under-reproduced and tended to over-produce target durations. Neither attention nor working memory predicted time reproduction and production performance. Conversely, when temporal variability was considered, participants' temporal variability in time production tasks was exclusively accounted for by age, whereas variability in temporal reproduction was also explained by divided attention and working memory. Overall, our results extend previous investigations on timing abilities in the elderly and underscore the importance of divided attention and working memory in the maintenance of a stable representation of durations.